Študijsko gradivo pri predmetu Pravni sistem in institucije EU: Zbirka vaj - Hojnik, Janja; Weingerl, Petra; Šuta, Živa (University of Maribor Press, 2024)
Study Material for the Course EU Legal System and Institutions: Collection of Exercises. This study material is intended for first cycle students at the Faculty of Law, University of Maribor, who are encountering EU law for the first time in the course The EU Legal System and Institutions. It offers a historical overview of the development of the EU and its supranational law and continues with a focus on the work of the EU institutions, with chapters following the ‘life-course’ of an EU act, from the question of EU competences to adopt the act and EU institutional structure to the legislative and non-legislative procedures and the legal effects of that act. This is followed by questions relating to the enforcement of EU law before the Court of Justice of the EU and national courts, and the EU Charter of Fundamental Rights. A chapter at the end of the material is devoted to selected issues of EU law, namely the rule of law and EU external relations. The material assesses and tests student’s knowledge through theoretical questions, points for discussion and practical examples.